Strongly Coupled Field Theories for Condensed Matter and Quantum Information Theory : proceedings, International Institute of Physics, Natal, Rn, Brazil, 2-21 August 2015 /: proceedings, International Institute of Physics, Natal, Rn, Brazil, 2-21 August 2015. (2020) - Unknown
No abstract available